Islamic Perspectives on Human, Happiness, and Technological Development - Zella Famelia; Ganang Junior; Anggita Hikmatul Hinayah; Hayu Nabila Ma’al Sukma; Nur Khikmah (al-Afkar, Journal For Islamic Studies, 2026)
Humans are humans themselves. as an 'abdullah and khalifah on earth who is equipped with reason by Allah to think and manage the universe in order to achieve happiness in this world and the hereafter. Islam does not prohibit humans from achieving it as long as it does not conflict with the concept of tauhidisasi, including the development of science and technology. This research seeks to find the relationship between religious concepts and the meaning of Islam to the concepts of humans and happiness, as well as their relevance in the development of science and technology. This research is a type of qualitative descriptive research using literature study methods and a philosophical approach. The data consists of primary and secondary data, then analyzed using the Miles and Huberman model. The research results found that: first, the concept of religion and the meaning of Islam towards the concept of humans and happiness are interconnected. Second, the concept of religion and the meaning of Islam regarding the concept of humans and happiness are very relevant in the development of science and technology. Islam leads the development of science and technology so that it does not discriminate between religions and opens up opportunities for humans to think about achieving happiness in this world and the hereafter by being grateful for what they have.